(untitled) (Наука и инновации, 2026)
This article analyzes the formation, historical stages of development, and current condition of technology education in general secondary schools. It explains how the subject initially emerged as labor education focused on manual skills and gradually evolved through the integration of scientific and technological advancements. The article also examines existing challenges in teaching technology education and outlines future prospects, including the implementation of modern technologies, innovative teaching methods, and interdisciplinary approaches. Special attention is given to the role of technology education in developing students’ practical, creative, and vocational skills.